PENGARUH VARIASI PRODUK, CITA RASA, DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG KONSUMEN ( Survei pada Kopi Janji Jiwa Karanganyar) - Hesti Yuliana; Adcharina Pratiwi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to analyze the significance of the influence of product variations, taste and service quality on consumer repurchase interest in kopi janji jiwa Karanganyar. The research uses primary data sources, with quantitative data types. The population in this research is the unknown number of kopi janji jiwa Karanganyar consumers. The number of samples used in this research was 100 respondents, using a purposive sampling technique. The data collection technique in this research used a questionnaire. The data analysis method uses descriptive analysis, multiple linear regression analysis, t test, F test (model accuracy) and R2 test. The research results show that product variations have a significant effect on Purchase Interest. Taste has a significant effect on repurchase interest. Service quality does not have a significant effect on repurchase intention.